MENINGKATKAN PENGUASAAN KOSAKATA SISWA MELALUI MEDIA FLASHCARD - Nabela, Siti (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
This study, conducted by Siti Nabela in 2023, investigates the effectiveness of using flashcards to improve vocabulary mastery among seventh-grade students at SMP Negeri 3 Ambawang Kubu Raya. The students faced challenges learning English vocabulary and differentiating grammatical forms such as nouns, verbs, adjectives, and adverbs. To address these issues, flashcards were implemented as a personal dictionary tool to enhance vocabulary learning, aiming to make students more active, motivated, and engaged in English classes. The research employed a Classroom Action Research (CAR) design, involving class VII A during the 2022/2023 academic year. Data were collected through interviews, observations, documentation, and tests across two cycles. The results indicated significant improvement in students' vocabulary mastery, with mean scores increasing from 45.70 in the pre-test to 70.52 in the first cycle post-test, and 80.13 in the second cycle post-test. The study concludes that flashcards effectively enhance students' vocabulary mastery, as evidenced by the rising test scores.